DOT1L Mediated Gene Repression in Extensively Self-Renewing Erythroblasts - Borosha, Shaon; Ratri, Anamika; Ghosh, Subhra; Malcom, Carrie A.; Chakravarthi, V. Praveen; Vivian, Jay L.; Fields, Timothy A.; Rumi, M. A. Karim; Fields, Patrick E. (Frontiers in Genetics, 2022)
DOT1L is essential for embryonic hematopoiesis but the precise mechanisms of its action remain unclear. The only recognized function of DOT1L is histone H3 lysine 79 (H3K79) methylation, which has been implicated in both transcriptional activation and repression. We observed that deletion of the mouse Dot1L gene (Dot1L-KO) or selective mutation of its methyltransferase domain (Dot1L-MM) can differentially affect early embryonic erythropoiesis. However, both mutations result in embryonic lethality by mid-gestation and growth of hematopoietic progenitor cells (HPCs) is similarly affected in extensively self-renewing erythroblast (ESRE) cultures established from yolk sac cells. To understand DOT1L-mediated gene regulation and to clarify the role of H3K79 methylation, we analyzed whole transcriptomes of wildtype and Dot1L-mutant ESRE cells. We observed that more than 80% of the differentially expressed genes (DEGs) were upregulated in the mutant ESRE cells either lacking the DOT1L protein or the DOT1L methyltransferase activity. However, approximately 40% of the DEGs were unique to either mutant group, indicating that DOT1L possesses both methyltransferase-dependent and -independent gene regulatory functions. Analyses of Gene Ontology and signaling pathways for the DEGs were consistent, with DEGs that were found to be common or unique to either mutant group. Genes related to proliferation of HPCs were primarily impacted in Dot1L-KO cells, while genes related to HPC development were affected in the Dot1L-MM cells. A subset of genes related to differentiation of HPCs were affected in both mutant groups of ESREs. Our findings suggest that DOT1L primarily acts to repress gene expression in HPCs, and this function can be independent of its methyltransferase activity.